Energy Security and Its Role in Regional Development: A ‎Probabilistic Assessment of Socio-Economic Indicators - Iurchenko, Maryna; Dzhegur , Gennadii; Kravchenko , Oleksandr Saliuk-; Velgan , Oleksandr; Yurchenko , Alla; Onysiuk, Serhii (International Journal of Basic and Applied Sciences, 2025)
Background: Energy security is widely recognized as a cornerstone for stable socio-economic development at the regional level. However, ‎traditional assessments often overlook the inherent uncertainties and volatilities associated with energy systems. This study addresses the ‎need for a more robust approach by incorporating probabilistic methods. Methods: A probabilistic modeling framework, utilizing Monte ‎Carlo simulations informed by historical data and expert elicitation, was developed to assess the impact of key energy security indicators ‎‎(supply diversity, import dependency, price volatility, infrastructure reliability) on core regional socio-economic metrics (GDP per capita ‎growth, unemployment rate, Human Development Index component). The framework was applied to a representative regional case study ‎under various energy security scenarios. Results: The probabilistic simulations revealed significant variability in socio-economic outcomes ‎contingent upon fluctuations in energy security parameters. Results indicated, for instance, a non-negligible probability (p=0.15) of negative ‎GDP growth under a simulated supply disruption scenario, compared to the baseline (p=0.05). Sensitivity analysis identified energy price ‎volatility and infrastructure reliability as having the most pronounced probabilistic impact on regional unemployment rates. Probability ‎distributions for key indicators under different scenarios were generated, quantifying the range and likelihood of potential socio-economic ‎impacts. Conclusions: The probabilistic assessment provides a more nuanced and realistic understanding of the energy security-regional ‎development nexus compared to deterministic approaches. It highlights the significant downside risks associated with energy insecurity and ‎underscores the importance of incorporating uncertainty into policy-making for resilient and sustainable regional development. The findings ‎emphasize the need for robust energy diversification and infrastructure investment strategies‎.
Keywords: Energy Security; Probabilistic Assessment; Regional Development; Socio-Economic Indicators; Public Administration